Cardioprotective effects of shock wave therapy: A cardiac magnetic resonance imaging study on acute ischemia-reperfusion injury - Petrusca, Lorena; Croisille, Pierre; Augeul, Lionel; Ovize, Michel; Mewton, Nathan; Viallon, Magalie (Frontiers in Cardiovascular Medicine, 2023)
Introduction Cardioprotection strategies remain a new frontier in treating acute myocardial infarction (AMI), aiming at further protect the myocardium from the ischemia-reperfusion damage. Therefore, we aimed at investigating the mechano-transduction effects induced by shock waves (SW) therapy at time of the ischemia reperfusion as a non-invasive cardioprotective innovative approach to trigger healing molecular mechanisms. Methods We evaluated the SW therapy effects in an open-chest pig ischemia-reperfusion (IR) model, with quantitative cardiac Magnetic Resonance (MR) imaging performed along the experiments at multiple time points (baseline (B), during ischemia (I), at early reperfusion (ER) (∼15 min), and late reperfusion (LR) (3 h)). AMI was obtained by a left anterior artery temporary occlusion (50 min) in 18 pigs (32 ± 1.9 kg) randomized into SW therapy and control groups. In the SW therapy group, treatment was started at the end of the ischemia period and extended during early reperfusion (600 + 1,200 shots @0.09 J/mm2, f = 5 Hz). The MR protocol included at all time points LV global function assessment, regional strain quantification, native T1 and T2 parametric mapping. Then, after contrast injection (gadolinium), we obtained late gadolinium imaging and extra-cellular volume (ECV) mapping. Before animal sacrifice, Evans blue dye was administrated after re-occlusion for area-at-risk sizing. Results During ischemia, LVEF decreased in both groups (25 ± 4.8% in controls (p = 0.031), 31.6 ± 3.2% in SW (p = 0.02). After reperfusion, left ventricular ejection fraction (LVEF) remained significantly decreased in controls (39.9 ± 4% at LR vs. 60 ± 5% at baseline (p = 0.02). In the SW group, LVEF increased quickly ER (43.7 ± 11.4% vs. 52.4 ± 8.2%), and further improved at LR (49.4 ± 10.1) (ER vs. LR p = 0.05), close to baseline reference (LR vs. B p = 0.92). Furthermore, there was no significant difference in myocardial relaxation time (i.e. edema) after reperfusion in the intervention group compared to the control group: ΔT1 (MI vs. remote) was increased by 23.2±% for SW vs. +25.2% for the controls, while ΔT2 (MI vs. remote) increased by +24.9% for SW vs. +21.7% for the control group. Discussion In conclusion, we showed in an ischemia-reperfusion open-chest swine model that SW therapy, when applied near the relief of 50′ LAD occlusion, led to a nearly immediate cardioprotective effect translating to a reduction in the acute ischemia-reperfusion lesion size and to a significant LV function improvement. These new and promising results related to the multi-targeted effects of SW therapy in IR injury need to be confirmed by further in-vivo studies in close chest models with longitudinal follow-up.